'The silent intermediary': a co-authored exploration of a client's experience of art psychotherapy for C-PTSD. Issue 1 (3rd April 2021) - Winter, Neil; Coles, Ali
ABSTRACT: Background: This article presents a client's (art therapee's) conceptualisation of his experience of art psychotherapy for symptoms of complex post-traumatic stress disorder (C-PTSD). Context: He was receiving treatment through a community adult mental health team within the UK National Health Service. Approach: The art therapee wrote about his art psychotherapy experience, and then he and his art psychotherapist identified key themes. They related his account to art psychotherapy theory and evidence and drew out implications of his experience for art psychotherapy research. Outcomes/Conclusions: The art therapee found that an art psychotherapy approach was helpful in these ways: having control; expressing without words; distancing from trauma; being creative and playful. He identified some aspects of the art psychotherapy which seem to be under-represented in art psychotherapy literature: the importance of the therapist's acceptance of the client's artwork for building trust; the way in which artmaking bypasses the fear of 'telling' about past abuse; and the therapeutic value of creativity and play for accessing positive aspects of the child self. Implications for research: It would be valuable to gain information from other clients with C-PTSD about their experiences of art psychotherapy. Research into the identified under-explored aspects of art psychotherapy practice, the use of artmaking for C-PTSD symptom management and how artmaking can be integrated within other approaches to C-PTSD treatment would be useful. Plain-language summary: This article describes how a client (art therapee) with symptoms of complex post-traumatic stress disorder (C-PTSD) experienced art psychotherapy. The art therapee received therapy through a UK National Health Service community adult mental health team. The therapy sessions were on a weekly basis over an 18-month period. The art therapee wrote about his art psychotherapy experience, and then he and his art psychotherapist identified some themes. They related his account to art psychotherapy theory and evidence and drew out implications of his experience for art psychotherapy research. The art therapee found that an art psychotherapy approach was helpful in four main ways. It helped him to feel in control of the therapeutic process, and enabled him to express experiences of past abuse without having to use words. It gave him a sense of distance from his traumatic experiences. Finally, it helped him to connect with his creativity. He identified some particular aspects of his experience which seem to be under-represented in art psychotherapy literature: the importance of the therapist's acceptance of the client's artwork for building trust; the way in which artmaking bypasses the fear of 'telling' about past abuse; and how creativity and playfulness in art psychotherapy sessions can enable a more positive view of oneself as a child. The authors consider that it would be valuable to gain information from other clients with C-PTSD about their experiences of art psychotherapy and to undertake research into those aspects of the client's experience which appear not to have been explored significantly so far. Research into how artmaking can help relieve C-PTSD symptoms and how artmaking might be used within other approaches to C-PTSD treatment would also be useful. Abstract :